Damage-control technology of oil-based drilling fluid for Kuqa piedmont structure. Issue 1 (2nd January 2018) - Xu, Peng; Tao, Zhengwu; Liu, Xiao; Yan, Zhihang; Xu, Mingbiao
Abstract: Oil-based drilling fluid is widely used in tight sandstone well and shale well in recent years, performance advantages of borehole stability and formation protection are the main reason to promote its use. According to the development and existing research, oil-based drilling fluid still existed serious damage, and could not catch the attention of developers. The study chose Keshen Block as the research object, analyzed reservoir characteristics, evaluated rock wettability, damage of oil-based drilling fluid and oil trapping, and analyzed damage mechanisms of oil-based drilling fluid. Based on the damage mechanisms and the characteristics of drilling fluid, the study analyzed the damage-control mechanisms, established optimization principle of oil-based drilling fluid, and optimized drilling fluid. Dynamic damage experiments and field application of drilling fluid showed that formation protection performance of optimized oil-based drilling fluid had improved significantly, and the formation damage caused by oil-based drilling fluid had been controlled effectively.